2010
DOI: 10.1172/jci43910
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple signaling pathways causes developmental defects in mice with a Noonan syndrome–associated Sos1 mutation

Abstract: Noonan syndrome (NS) is an autosomal dominant genetic disorder characterized by short stature, unique facial features, and congenital heart disease. About 10%-15% of individuals with NS have mutations in son of sevenless 1 (SOS1), which encodes a RAS and RAC guanine nucleotide exchange factor (GEF). To understand the role of SOS1 in the pathogenesis of NS, we generated mice with the NS-associated Sos1E846K gain-offunction mutation. Both heterozygous and homozygous mutant mice showed many NS-associated phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 67 publications
9
79
0
Order By: Relevance
“…In agreement with this, earlier reports incidentally showed that Mek inhibitors can rescue growth defect in other NS mouse models (RAF1 L613V/+ and SOS1 E846K/E846K ) [7,66]. Altogether, these reports suggest that pharmacological regulation of Ras/MAPK could be an alternative approach to treat short stature in NS patients, even though a lot requires to be accomplished to assess the efficacy and safety of these Figure 1.…”
Section: Role Of Ptpn11/shp2 Mutant Causing Ns In Ras/mapk Upregulatisupporting
confidence: 67%
See 1 more Smart Citation
“…In agreement with this, earlier reports incidentally showed that Mek inhibitors can rescue growth defect in other NS mouse models (RAF1 L613V/+ and SOS1 E846K/E846K ) [7,66]. Altogether, these reports suggest that pharmacological regulation of Ras/MAPK could be an alternative approach to treat short stature in NS patients, even though a lot requires to be accomplished to assess the efficacy and safety of these Figure 1.…”
Section: Role Of Ptpn11/shp2 Mutant Causing Ns In Ras/mapk Upregulatisupporting
confidence: 67%
“…However, in the cell or in vivo, these mutations result almost systematically in a higher-than-normal activation of the Ras/ MAPK pathway. This hyperactivation is thought to be responsible for the disease phenotype, as shown by studies in mice which began to explore the mechanisms involved in the pathogenicity of genes causing NS or other Rasopathies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the causative allele in each NS patient is likely to be critical for choosing an effective therapy. For example, mice that carry a Sos1 mutation develop multiple NS features, and these defects can be prevented or their expression reduced by MEK inhibitor treatment during the early stages of life (47). Postnatal MEK inhibitor treatment also reverses some NS symptoms in Raf1 mutant mice (48), and rapamycin normalizes HCM in LS mouse models (5).…”
Section: Significancementioning
confidence: 99%
“…RTK activation engenders RAS signaling to be turned on through GRB2, which has been implicated in the development of hypertrophy (46). In turn, GRB2 mediates the activation of SOS1, which is mutated in NS patients and mouse models leading to HCM (47). Also, SHP2 is a key component of multiple RTK, cytokine receptor and integrin signaling cascades.…”
Section: Pathophysiological Signaling: Experimental Relevance Of the mentioning
confidence: 99%